Perancangan Media Pembelajaran Matematika Berbasis Android menggunakan Smart Apps Creator 3 - Abdul Majid; Rasmanto Rasmanto (APTIKOM SUMSEL, 2022)
The development of increasingly advanced technology lately has an influence not only on human social life but also on education. On the other hand, many schools still use conventional learning systems. Based on observations at Muhammadiyah Wiradesa Middle School, the authors obtained information that students were less interested in conventional learning methods. Therefore, to increase students' learning motivation, it is necessary to innovate in learning. The development of android-based learning media is one of the efforts to create creative learning by utilizing technology. The method in this study is Research and Development (RnD) with the ADDIE development model, data collection techniques using interviews, questionnaires, and tests. The results showed that the product development produced by the researchers obtained a good score with an average score of 67 or 89.33% according to material experts. Then, according to media experts, the score is 69 or 92% with the criteria of